مراتب الوازع وأثرها في تعميق فقه المواطنة - بن حرز الله, عبد القادر; موفـق, نبيــل (Sciences humaines; Vol. 35 (2014): SCIENCES HUMAINES)
ناقشت في هذا المقال إشكالية حراسة قواعد ومبادئ فقه المواطنة انطلاقاً من الوازع ومراتبه، فتحدّثت عن معنى الوازع، وعن مراتبه، والتي هي الوازع الجبلّي، والوازع الدّيني، والوازع السّلطاني، وارتباط هذه المفاهيم بقيم المواطنة.      ثمّ بحثت المبادئ والأسس الكبرى التي يقوم عليها فقه المواطنة، ودور مراتب الوازع في حراستها، وفي تكوين ثقافة عامة شاملة، تنطلق من مجالات الاستعدادات النّفسية والطّبيعيّة للإنسان، والمتمثّلة في الفطرة، والمعتقدات الدّينيّة، والقوانين الوضعيّة الموجّهة للسّلوك الإنساني.       وختمت المقال بإطلالة مختصرة  عن آثار العولمة في سلامة المنظومة التّربويّة والتّعليميّة، والتي تعتبر قطب الرّحى في فقه المواطنة، وأشرت إلى دور الوازع في الحدّ من هذه الآثار السّلبيّة              In this essay I discussed the problematic  that deals with the effective protectivity and guarding  of   the bases and principles of the citizenship doctrine , starting from the religious obligation and its classes ; in which I dealt with its  meaning first, its classifications which infact are : the innate stimulus, the spiritual stimulus and finally the authoritative one ; and their  effects  and relative concepts  with the citizenship values.     Then I studied the large basis and principles  upon which the doctrine of citizenship is founded ; and the role of the stimulus in its protection on the one hand, and the forming of a comprehensive general  culture on the other hand ;   begining with the  different  perspectives of the psychlogical and natural  readiness   of the human being, That is shown in the innate instinct , the spiritual beliefs and the posited laws destined to the human behaviour.     In the end, I concluded my essay with a quick flash back on the  effects ot the  globalization in the educational system’s safety, which is infact the pivot of the mill in the citizenship doctrine . I also mentioned  the role of prevention from these negative effects.